Value-driven career attitude and job performance: An intermediary role of organizational citizenship behavior - Iqbal, Muhammad Babar; Li, Jianxun; Yang, Shuili; Sindhu, Paras (Frontiers in Psychology, 2022)
Background: Value-driven career attitude (VDCA) is considered a dimension of a protean career attitude (PCA). Individuals with this attitude seek out personally meaningful experiences and set their own psychological career success standards. This study investigates the association between value-driven career attitude and job performance. It looks at how organizational citizenship behavior affects the relationship between value-driven career attitudes and job performance. Methods: A self-reported questionnaire was used to collect data from 400 random employees of SMEs in Pakistan during the early pandemic. We chose Cochran’s formula to determine the appropriate sample size, and PLS-SEM was used to analyze the model. P-O fit and self-determination theory is the theoretical lenses used in this study. The underpinning theories to this study enable the researcher to establish a link between VDCA, OCB, and job performance. Results: By analyzing a sample of 400 employees from active enterprises, we discover that VDCA contributes to an improvement in job performance. Furthermore, OCB plays an intervening effect in the relationship between VDCA and job performance. Thus, the study provided evidence for the underpinning models of P-O fit and self-determination theory. Conclusion: This study adds to the body of knowledge by investigating the connections between VDCA, OCB, and job performance in SMEs. The existing literature sheds scant light on these linkages, leaving a gap that this study will address. The current study expands on other themes to provide an in-depth analysis of many under-explored PCA outcomes, which may open up new avenues for future researchers to broaden and strengthen PCA with other constructs.